2018
DOI: 10.1038/s41420-018-0049-2
|View full text |Cite
|
Sign up to set email alerts
|

KPT-330 inhibition of chromosome region maintenance 1 is cytotoxic and sensitizes chronic myeloid leukemia to Imatinib

Abstract: As tyrosine kinase inhibitors (e.g., Imatinib, IM) fail to induce long-term response in some chronic myeloid leukemia (CML), novel therapies targeting leukemia-dysregulated pathways are necessary. Nuclear-cytoplasmic trafficking of proteins play a key role in the development of leukemia and drug resistance. KPT-330 (Selinexor), an inhibitor of chromosome region maintenance 1 (CRM1, nuclear receptor exportin 1, XPO1), demonstrated activities against a few hematological malignancies. We examined the anti-leukemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…38 Previous studies have shown that KPT-330 single agent treatment leads to G 0 /G 1 cell cycle arrest and some have reported that KPT-330 single agent treatment could result in decreased expression of CRM1 and Rad51, leading to a DNA damage phenotype. 8,[39][40][41][42][43][44][45][46][47][48][49][50] Further, in MCL cell lines, KPT-330 has been shown to induce G 0 /G 1 phase arrest and could overcome inherit ibrutinib resistance through NFkB inhibition. 51 In our experimental model, we did not find a significant decrease in CRM1 or Rad51 expression with single agent KPT-330 treatment ( Figure 4G and supplemental Figure 1B).…”
Section: Discussionmentioning
confidence: 99%
“…38 Previous studies have shown that KPT-330 single agent treatment leads to G 0 /G 1 cell cycle arrest and some have reported that KPT-330 single agent treatment could result in decreased expression of CRM1 and Rad51, leading to a DNA damage phenotype. 8,[39][40][41][42][43][44][45][46][47][48][49][50] Further, in MCL cell lines, KPT-330 has been shown to induce G 0 /G 1 phase arrest and could overcome inherit ibrutinib resistance through NFkB inhibition. 51 In our experimental model, we did not find a significant decrease in CRM1 or Rad51 expression with single agent KPT-330 treatment ( Figure 4G and supplemental Figure 1B).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, BCR‐ABL localization was examined mostly by immunofluorescent detection of exogenous proteins with Abs against BCR and/or c‐ABL 35‐37 . However, this experimental system cannot distinguish BCR‐ABL from normal BCR and c‐ABL proteins derived from residual alleles.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, BCR-ABL localization was examined mostly by immunofluorescent detection of exogenous proteins with Abs against BCR and/or c-ABL. [35][36][37] However, this experimental system cannot distinguish BCR-ABL from normal BCR and c-ABL proteins derived from residual alleles. To circumvent this issue, we generated a BCR-ABL junction-specific Ab to detect only the e14a2-type BCR-ABL protein by immunocytochemistry ( Figure S2).…”
Section: Autophagy Is Associated With Cytoplasmic Translocation Andmentioning
confidence: 99%
“…For a variety of solid tumors, overexpression of CRM1 has been shown. In patients with osteosarcoma and in preclinical models of hepatocellular carcinoma cell lines, a correlation between the expression of CRM1 and cancer proliferation was demonstrated (Yao et al 2009 ; Zheng et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%